PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA SATE TAICHAN BANG SATE CIPUTAT TANGERANG SELATAN - Faishal Farras Husain; Ahyani (Journal of Research and Publication Innovation, 2025)
This research aims to influence product quality and price on purchasing decisions at Sate Taichan Bang Sate Ciputat Branch, South Tangerang. The method used is quantitative methods. The population in this study were consumers of Sate Taichan Bang Sate Pamulang Branch with a total of 6490 people. The sampling technique used is probability sampling, namely a sampling method using the Slovin formula. The research sample was 98 respondents. Data analysis methods used in research include instrument tests consisting of validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity and autocorrelation tests, multiple linear regression tests, correlation coefficients, hypothesis tests consisting of t tests. partially and simultaneously f test, and coefficient of determination test. From the results of this research it can be concluded that product quality has a positive and significant influence on purchasing decisions with a value of T_count > T_table or (15.512> 1.985) and is strengthened by a significance value of 0.000 < 0.05. Thus, 〖Ho〗_1 is rejected and H_1 is accepted. Price has a positive and significant influence on purchasing decisions with a value of T_count > T_table or (15.702 > 1.985) and is strengthened by a significance value of 0.000 < 0.05. Thus, 〖Ho〗_2 is rejected and H_2 is accepted. Product quality and price have a positive and significant influence on purchasing decisions with a value of F_count > F_table or (153.190 > 3.090) and is strengthened by a significance value of 0.000 < 0.05. Thus, 〖Ho〗_3 is rejected and H_3 is accepted. Product quality and price on purchasing decisions influence regression Y = 4.710 + 0.437 X1 + 0.462 X2 + α. The resulting R-square value (coefficient of determination) is 0.763, so it can be concluded that the product quality (X1) and price (X2) variables together have an influential contribution to the purchasing decision variable (Y) of 76.3% while the remaining is 23 , 7% is influenced by other factors or variables not studied.